Peranan Media Platform Sebagai Sarana Promosi Perpustakaan Di Era Revolusi 4.0 - Mas Adi Sawitri, Ni Luh Putu Ayu; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 1 No 1 (2021), 2021)
This research purposes to describe the role of platform media as a tool of promoting library in revolution industry era of 4.0. The study used library research since the data was collected through books, jurnals, and other sources. The data were analysed by descriptive qualitative method using data collection, data reduction, data display and verification. The data were collected by reading several sources, analyzing, and concluding the results. The results found that there are several media platforms that can be used in promoting library i.e. social media such as Instagram, WhatsApp, Twitter, Youtube and Website. Besides, there are several problems may occur in promoting library using media platform such as the limitation of human resources, unstable internet connection and collection of resources in the library.    Keywords : Platform media, revolution 4.0, promotion, library.